Warm-up effects on muscle oxygenation, metabolism and sprint cycling performance - Wittekind, A.; Cooper, C. E.; Elwell, C. E.; Leung, T. S.; Beneke, R. (European Journal of Applied Physiology, 2012)
To investigate the effects of warm-up intensity on all-out sprint cycling performance, muscle oxygenation and metabolism, 8 trained male cyclists/triathletes undertook a 30-s sprint cycling test preceded by moderate, heavy or severe warm up and 10-min recovery. Muscle oxygenation was measured by near-infrared spectroscopy, with deoxyhaemoglobin ([HHb]) during the sprint analysed with monoexponential models with time delay. Aerobic, anaerobic-glycolytic and phosphocreatine energy provision to the sprint were estimated from oxygen uptake and lactate production. Immediately prior to the sprint, blood [lactate] was different for each warm up and higher than resting for the heavy and severe warm ups (mod. 0.94 ± 0.36, heavy 1.92 ± 0.64, severe 4.37 ± 0.93 mmol/l P < 0.05), although muscle oxygenation was equally raised above rest. Mean power during the sprint was lower following severe compared to moderate warm up (mod. 672 ± 54, heavy 666 ± 56, severe 655 ± 59 W, P < 0.05). The [HHb] kinetics during the sprint were not different among conditions, although the time delay before [HHb] increased was shorter for severe versus moderate warm up (mod. 5.8 ± 0.6, heavy 5.6 ± 0.9, severe 5.2 ± 0.7 s, P < 0.05). The severe warm up was without effect on estimated aerobic metabolism, but increased estimated phosphocreatine hydrolysis, the latter unable to compensate for the reduction in estimated anaerobic-glycolytic metabolism. It appears that despite all warm ups equally increasing muscle oxygenation, and indicators of marginally faster oxygen utilisation at the start of exercise following a severe-intensity warm up, other energy sources may not be able to fully compensate for a reduced glycolytic rate in sprint exercise with potential detrimental effects on performance.